Epigenetic alteration of Wnt pathway antagonists in progressive glandular neoplasia of the lung - Licchesi, Julien D.F. (Oxford University Press, 2008)
Background: Atypical adenomatous hyperplasia (AAH) is now recognized as a precursor lesion from which lung adenocarcinomas arise and thus represents an ideal target for studying the early genetic and epigenetic alterations associated with lung tumorigenesis such as alterations of the Wnt pathway. Methods: We assessed the level of Wnt signaling activity in lung cancer cell lines by determining the level of active β-catenin and determined the level of expression of Wnt antagonists APC, DKK1, DKK3, LKB1, SFRP1, 2, 4, 5, WIF1 and RUNX3 using reverse transcription–polymerase chain reaction. Using multiplex nested methylation-specific polymerase chain reaction, we analyzed promoter region methylation of these genes in resected lung tissue in the histopathologic sequence of glandular neoplasia (normal lung parenchyma, low-grade and high-grade AAH, adenocarcinoma). Results: The majority of non-small cell lung cancer cell lines (11 of 16, 69%) have evidence of active Wnt signaling and silencing of Wnt antagonists correlated with promoter hypermethylation. Promoter region methylation of Wnt antagonists was common in primary lung adenocarcinoma and there was a significant increase in the frequency of methylation for Wnt antagonist genes and the number of genes methylated with each stage of tumorigenesis (test for rend P ≤ 0.01). Additionally, odds ratios for promoter hypermethylation of individual or multiple Wnt antagonist genes and adenocarcinomas were statistically significantly elevated and ranged between 3.64 and 48.17. Conclusion: These results show that gene silencing of Wnt antagonists by promoter hypermethylation occurs during the earliest stages of glandular neoplasia of the lung and accumulates with progression toward malignancy.